2006
DOI: 10.1523/jneurosci.3815-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1, a Novel Cytokine-Like Mediator Linking Acute Neuronal Death and Delayed Neuroinflammation in the Postischemic Brain

Abstract: Cerebral ischemic injury proceeds with excitotoxicity-induced acute neuronal death in the ischemic core and with delayed damage processes in the penumbra. However, knowledge concerning the direct mediators that connect these two processes is limited. Here, we demonstrate that high-mobility group box 1 (HMGB1), a nonhistone DNA-binding protein, is massively released into the extracellular space immediately after ischemic insult and that it subsequently induces neuroinflammation in the postischemic brain. Short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
488
3
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 521 publications
(510 citation statements)
references
References 38 publications
(47 reference statements)
17
488
3
2
Order By: Relevance
“…The presence of HMGB-1 in rat cisterna magna fluid probably reflects its release and diffusion from ischemic tissue. We did not detect any HMGB-1 in mouse plasma in contrast to a study in the rat (Kim et al, 2006).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The presence of HMGB-1 in rat cisterna magna fluid probably reflects its release and diffusion from ischemic tissue. We did not detect any HMGB-1 in mouse plasma in contrast to a study in the rat (Kim et al, 2006).…”
Section: Discussioncontrasting
confidence: 99%
“…Here, we suggest that HMGB-1 is released from the ischemic brain parenchyma within 1 h after MCAO, based on early loss of HMGB-1 immunoreactivity in the striatum. Kim et al (2006) showed that HMGB-1 was not hyperacetylated, suggesting that its release is passive. Our demonstration that HMGB-1 is present in rat CSF is also in agreement with Kim et al (2006), who detected this protein 3 h after transient MCAO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that the high-mobility group box 1 (HMGB1) protein, an abundant nuclear protein that acts as an architectural chromatin binding factor, can be passively released by necrotic or damaged cells and serves as a signaling molecule that is involved in acute and chronic inflammation [9,10] . A wealth of evidence indicates that HMGB1 is massively released during the excitotoxicityinduced, acute damaging process in the post-ischemic brain, where it triggers inflammatory processes, and suggests that HMGB1 acts as a novel mediator that links excitotoxicityinduced acute damage and subsequent inflammatory processes in the post-ischemic brain [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…In damaged tissue, extracellular HMGB1 acts as a necrotic signal, which alerts the surrounding cells and the immune system. 2 Although extracellular HMGB1 can contribute to normal tissue development and repair, it is also implicated in the pathogenesis of several diseases (including lethal endotoxemia, 7 disseminated intravascular coagulation, 9 ischemic brain, 10 tumor, 11 atherosclerosis, 12 rheumatoid arthritis, 13 and periodontitis 14 ).…”
mentioning
confidence: 99%